Determinants of Property Prices in Hong Kong SAR : Implications for Policy - Craig, R.; Hua, Changchun (Washington, D.C. : International Monetary Fund, 2011)
This paper uses an econometric model of residential property prices in Hong Kong SAR to assess the effectiveness of alternative policies in slowing the increase in property prices. The rapid rise in property prices is well explained by macroconomic fundamentals; real GDP per capital, real domestic credit, construction costs, land supply, and the real interest rate. Policy can influence the property market though land supply and prudential and tax policy, with the latter policies taking the form of a stamp duty on property transactions and a tighter loan-to-value ratio (LTV) on lending. Land supply is the most effective policy insturment for restraining property price increases but it operates with a significant lag. The LTV and stamp duty dampen speculative activity that drives up property prices. While these policies can slow the increase in the short run, they should be guided by their long run objectives of financial stability and counteracting speculation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Hong Kong Special Administrative Region, People's Republic of China